Impact of continuous intraoperative vagus stimulation on intraoperative decision making in favor of or against bilateral surgery in benign goiter. Issue 4 (August 2019) - Schneider, Rick; Machens, Andreas; Randolph, Gregory; Kamani, Dipti; Lorenz, Kerstin; Dralle, Henning
Abstract : The advent of continuous vagus stimulation (CVS), eliminating lag time between nerve preparation with potential trauma and stimulation, has transformed the intraoperative surgical strategy in thyroid surgery. Continuous intraoperative nerve monitoring empowers the surgeon to be optimally aware of traction-related injury to the recurrent laryngeal nerve (RLN). Electromyographic precursor lesions, called combined events, prompt surgeons to cease harmful surgical maneuvers and release the nerve before damage to the nerve is established. Complete RLN recovery, defined as restitution of the nerve amplitude to ≥50% of baseline, assures the surgeon that it is safe to pursue completion surgery of the contralateral side in one procedure. If this restitution is incomplete or absent (<50% of amplitude baseline) immediate vocal cord paralysis is likely and it is advisable to delay completion surgery until the nerve has fully recovered. This review summarizes the tremendous progress made in this dynamic field, delineating the extent to which CVS has changed the landscape: tailoring intraoperative decision making to determine the safest course of action for patients with benign goiter.